Tick repellents and acaricides of botanical origin: a green roadmap to control tick-borne diseases? - Benelli, Giovanni; Pavela, Roman; Canale, Angelo; Mehlhorn, Heinz (Parasitology research, 2016)
Arthropods are dangerous vectors of agents of deadly diseases, which may hit as epidemics or pandemics in the increasing world population of humans and animals. Among them, ticks transmit more pathogen species than any other group of blood-feeding arthropods worldwide. Thus, the effective and eco-friendly control of tick vectors in a constantly changing environment is a crucial challenge. A number of novel routes have been attempted to prevent and control tick-borne diseases, including the development of (i) vaccines against viruses vectored by ticks; (ii) pheromone-based control tools, with special reference to the "lure and kill" techniques; (iii) biological control programmes relying on ticks' natural enemies and pathogens; and (iv) the integrated pest management practices aimed at reducing tick interactions with livestock. However, the extensive employment of acaricides and tick repellents still remains the two most effective and ready-to-use strategies. Unfortunately, the first one is limited by the rapid development of resistance in ticks, as well as by serious environmental concerns. On the other hand, the exploitation of plants as sources of effective tick repellents is often promising. Here, we reviewed current knowledge concerning the effectiveness of plant extracts as acaricides or repellents against tick vectors of public health importance, with special reference to Ixodes ricinus, Ixodes persulcatus, Amblyomma cajennense, Haemaphysalis bispinosa, Haemaphysalis longicornis, Hyalomma anatolicum, Hyalomma marginatum rufipes, Rhipicephalus appendiculatus, Rhipicephalus (Boophilus) microplus, Rhipicephalus pulchellus, Rhipicephalus sanguineus and Rhipicephalus turanicus. Eighty-three plant species from 35 botanical families were selected. The most frequent botanical families exploited as sources of acaricides and repellents against ticks were Asteraceae (15 % of the selected studies), Fabaceae (9 %), Lamiaceae (10 %), Meliaceae (5 %), Solanaceae (6 %) and Verbenaceae (5 %). Regression equation analyses showed that the literature grew by approximately 20 % per year (period: 2005-2015). Lastly, in the final section, insights for future research are discussed. We focused on some caveats for future data collection and analysis. Current critical points mainly deal with (a) not uniform methods used, which prevent proper comparison of the results; (b) inaccurate tested concentrations, frequently 100 % concentration corresponded to the gross extract, where the exact amounts of extracted substances are unknown; and (c) not homogeneous size of tested tick instars and species. Overall, the knowledge summarized in this review may be helpful for comparative screening among extensive numbers of plant-borne preparations, in order to develop newer and safer tick control tools.
Keywords: Livestock; zvířata; hluchavkovité; kontrola klíšťat; Ixodidae; nemoci přenášené klíšťaty; Acaricides; rostlinné extrakty; Disease Vectors; Tick Control; klíště; Argasidae; Asteraceae; Lamiaceae; Animals; Plant extract; Icaridin; Ixodes; Biosafety; DEET; akaricidy; infekce přenášené vektorem; Rickettsiales; dobytek; Fabaceae; Rhipicephalus sanguineus; Tick-Borne Diseases; Arbovirus; Lyme disease; Plant Extracts